Ἐμπειρία, πόλεμος y ἱστορíα en el método historiográfico de Polibio - José Vela Tejada (Talia dixit, 2014)
The historiographical approach of Polybius’Pragmatic History attracts our attention to wards the experience and professional training of literary authors and protagonists of his account: in particular, political and military issues. In our opinion, Polybius’ Histories must be understood as been writing by a seasoned military historian, as can be seen particularly in the report of military events